Analisis Kepuasan Konsumen Terhadap Produk Dan Pelayanan Seblak Rorongkong Teh Memey Kota Bogor - Putri Sakti Fujiyanti A.; Raisa Fasya; Viona Kesya Sundari; Ghaisya Raihana; Ilham Fauzi; Khoirul Aziz Husyairi; Tina Nur Ainun; Ai Imas Faidoh Fatimah (PUSAT SAINS INDONESIA, 2023)
This research is based on the tendency of consumers to consume spicy food in Bogor City, namely Seblak. Seblak is a spicy food that is in great demand by teenagers to adults. Seblak comes from the word